The Impact of Neoliberal Policies on Historic Urban Space: Areas of Urban Renewal in Istanbul - Dincer, Iclal (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2011)
The state's role in recasting urban space in Turkey entered a new phase during the last decade. The key difference compared with the past is that the inner city has now become the main source of capital accumulation. Interventions based on the rationale of clearing away obsolescent urban space to encouraging capital accumulation by private investors have led to the loss not only of local incomes but also of the cultural capital of local inhabitants. In addition, historical urban housing areas are no longer seen as 'common public assets' and designated renewal areas are not viewed as society's common cultural capital. This paper focuses on restructuring policies in historical urban spaces in Istanbul, as authorised by the Law on Renewal enacted in 2005. This law essentially defines the designation of renewal areas, instructions for preliminary and application projects, and the processes of organization, management, supervision, participation, and use. The paper critically analyses the ways local municipalities have made the use of the new legal framework on the basis of four case studies from Istanbul; namely, Sulukule, Tarlabasi, Suleymaniye and Fener-Balat renewal areas.
Keywords: Public Administration